Fine Motor Development in Improving the Writing Ability of Autistic Children in Primary School, Age 9 Years old - Natalia Veronica; Tati Hernawati; Imas Diana Aprilia (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2026)
Writing skills are an important aspect of children's academic development, including those with disability such as children with autism spectrum disorder (ASD). This research analyzes the effects of fine motor development on children with autism's writing ability, identifies the factors, and designs effective, applicable interventions. This research uses to descriptive qualitative approach with a single case study method. The study population consisted of 9-year-old children diagnosed with ASD at High Five Preschool Academy. The sample consisted of 10 children, selected through purposive sampling. The research subject was a 9-year-old boy who was diagnosed with autism and had writing barriers. The writing results were analyzed descriptively to evaluate neatness, letter-shape accuracy, and consistency over time. This technique was chosen because it can describe the in-depth meaning of the subject's experiences and responses during the learning process. This finding strengthens the results of previous research. It adds new insights into the effectiveness of individualized learning programs (IOPs) designed in a structured, multisensory, and collaborative manner among teachers, parents, and experts. In conclusion, fine motor development significantly improves children with autism writing skills.